Efficacy of silver ions against Sacbrood virus infection in the Eastern honey bee Apis cerana - Ahn, Ah-Jin; Ahn, Kyu-Sung; Suh, Guk-Hyun; Noh, Jin-Hyeong; Kim, Young-Ha; Yoo, Mi-Sun; Kang, Seung-Won; Shin, Sung-Shik (Journal of veterinary science (Suwŏn-si, Korea), 2015)
Although silver is known to be a broad-spectrum biocidal agent, the effects of this metal against Sacbrood virus have not yet been investigated. In this study, we evaluated the efficacy of silver ions against natural Korean sacbrood virus (KSBV) infection of Apis (A.) cerana. Ten KSBV-infected colonies containing A. cerana with similar strength and activity were selected from an apiary located in Bosung-gun (Korea). Among these, five colonies were randomly assigned to the treatment group that was fed sugar syrup containing 0.2 mg/L silver ions. The other colonies were assigned to the untreated control group in which bees were given syrup without the silver ions. To assess the efficacy of the silver ions, colony strength, colony activity, and the number of dead larvae per hive were measured. During the experimental period, the test group maintained its strength and activity until day 32 while those of bees in the control group decreased sharply after day 8 to 16. Survival duration of the test group was significantly longer (40 days) than that of the control group (21 days). These results strongly indicated that silver ions are effective against KSBV infection in A. cerana.